2023
DOI: 10.1186/s12951-023-01856-9
|View full text |Cite
|
Sign up to set email alerts
|

Isoginkgetin-loaded reactive oxygen species scavenging nanoparticles ameliorate intervertebral disc degeneration via enhancing autophagy in nucleus pulposus cells

Abstract: Excessive reactive oxygen species (ROS) in nucleus pulposus cells (NPCs) promote extracellular matrix (ECM) degradation and cellular inflammatory responses by activating a variety of cellular pathways, ultimately inducing cell apoptosis and leading to the development of low back pain. Here, we designed and fabricated an isoginkgetin-loaded ROS-responsive delivery system (IGK@SeNP) based on diselenide block copolymers. Successfully encapsulated IGK was released intelligently and rapidly in a microenvironment wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…It has shown promise as a potential therapeutic agent for IVDD. In a study conducted by Yu et al, a selenium–selenium (Se–Se) bond-containing nanodelivery system was developed to carry IGK (IGK@SeNP). This delivery system exhibited ROS-responsiveness and demonstrated excellent biocompatibility.…”
Section: Therapeutic Agent Therapy For Ivddmentioning
confidence: 99%
See 1 more Smart Citation
“…It has shown promise as a potential therapeutic agent for IVDD. In a study conducted by Yu et al, a selenium–selenium (Se–Se) bond-containing nanodelivery system was developed to carry IGK (IGK@SeNP). This delivery system exhibited ROS-responsiveness and demonstrated excellent biocompatibility.…”
Section: Therapeutic Agent Therapy For Ivddmentioning
confidence: 99%
“…Demonstration of inflammation suppression and restoration of ECM homeostasis in IVDD rat models. Reproduced with permission from Wang et al 38 49 a selenium−selenium (Se−Se) bond-containing nanodelivery system was developed to carry IGK (IGK@SeNP). This delivery system exhibited ROS-responsiveness and demonstrated excellent biocompatibility.…”
Section: Small-molecule Drug Delivery System 311 Anti-inflammatory An...mentioning
confidence: 99%
“…Yu et al constructed a ROS-responsive IGK-loaded nanodelivery system (IGK@SeNP) and achieved its smart release under the stimulation of excessive ROS. 89 The IGK@SeNP system contained Se-Se bonds and exhibited excellent biocompatibility. Se-Se bonds and IGK play a joint role in clearing ROS.…”
Section: Internal Stimuli-responsive Delivery Systems For Ivddmentioning
confidence: 99%
“…Further testing in a rat needle puncture IVDD model showed that this intelligent system has superior efficacy for treating IVDD in vivo. 89 …”
Section: Internal Stimuli-responsive Delivery Systems For Ivddmentioning
confidence: 99%
See 1 more Smart Citation